Breast cancer: the real road of the Brazilian northeast - Castro e Silva, I. M.; Viègas, M. V.; da Silva Pires, A. M.; Penteado Lancellotti, C. L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Objective. To characterize the clinical and sociodemographic aspects of breast cancer patients undergoing cancer treatment in the State of Maranhão, in a public reference hospital. Methods. Descriptive, correlational and analytical cross-sectional study, conducted between January 2019 and February 2020, at the Tarquínio Lopes Filho State Cancer Hospital. The study population consisted of all women, in first consultation, with breast cancer undergoing chemotherapy, in agreement with the study and with no brain metastasis evidenced. Statistical analysis was performed using SPSS v. 19 software, considering a significance level of 5%. Results. Eighty adult women were part of the study, whose average age was 52.54. Most of the women were born in São Luís, white, housewives, sedentary, married, former smokers, and Catholic. They had technical/ specialized training. In the clinical results, the histological type of infiltrative ductal carcinoma predominated, as well as stage III, mastectomy and the doxorubicin-cyclophosphamide-taxol chemotherapy regimen. Conclusion. The knowledge of each regional profile assists health professionals regarding the characterization of a target population and the design of targeted preventive and self-care strategies by managers.